Restoration of the mycobiome of the endangered Hawaiian mint Phyllostegia kaalaensis increases its resistance to a common powdery mildew. (August 2021) - Egan, Cameron P.; Koko, Jerry H.; Muir, Christopher D.; Zahn, Geoffrey; Swift, Sean O.I.; Amend, Anthony S.; Hynson, Nicole A.
Abstract: Beneficial microbes such as plant mutualistic fungi, hold the promise of ameliorating challenges faced in native plant conservation such as disease management. As an alternative to costly chemical pest control, conservation efforts could potentially harness the benefits of plant mutualistic fungi to aid in defense and disease resistance, but there are few tests of this notion. We set out to test the efficacy of controlling a common foliar pathogen, the powdery mildew Neoerysiphe galeopsidis, by inoculating the endangered Hawaiian plant species Phyllostegia kaalaensis with potentially beneficial members of its wild-type mycobiome. We tested whether inoculating plants with above or belowground fungal mutualists, or both, led to increased disease resistance in the host. We found that while all treatments reduced average disease incidence, colonization by the foliar yeast Moesziomyces aphidis was the only treatment to do so significantly. These results provide an exciting new strategy for plant conservation practices. Highlights: Plant associated beneficial fungi are an untapped tool in plant conservation. Fungi aid in disease resistance in an endangered Hawaiian plant species. Leaf fungi aid in defense against a leaf pathogen more than root associated fungi.